PENGARUH RASIO KARBON-NITROGEN DALAM ENSILAGE CAMPURAN MUKUNA LOKAL (MUCUNA SP) DAN RUMPUT KUME (SORGHUM PLUMOSUM VAR. TIMORENSE) SEGAR TERHADAP KANDUNGAN NUTRISI PRODUK (The effects of carbon-nitrogen ratio in ensilage of local mucuna (mucuna sp.) And... - Vinensius Darmin; Twenfosel O. Dami Dato; Marthen Luther Mullik (JURNAL NUKLEUS PETERNAKAN, 2022)
The main problem in preservation of protein source forages in silage making is spoilage due to high buffering characteristic of protein. This might relates to low carbon-nitrogen (C-N) ratio in these plants. This study aimed at determining the best level of C-N ratio in ensilage process of a grass-legume mixture. A 3x4 completely randomized design (CRD) was deployed to test three C-N ratio levels as treatments. The treatments were CN20 (Mucuna sp + kume grass + rice bran to reach C-N ratio of 20, or 30 (CN30) or 40 (CN40). Variables measured were dry matter (DM), organic matter (OM), crude protein (CP), ether extract (EE), and crude fiber (CF) content of the silage. Data were analyzed using General Linear Model for CRD with an alfa value of 0.05. Treatment differences were determined using Duncan test. The results showed that C-N ratio had high significant effects on DM content (ranged from 22.5 to 32.0%), and CP content (ranged from 7.5 to 9.6%). Significant treatment effects were detected in OM content (ranged from 90.5 to 91.8%), and EE content (ranged from 2.82 to 3.66%). Meanwhile, CF was not effected by C-N ratio (ranged from 39.0 to 3.0%. 44.2%). It could be concluded that C-N the ratio of 30 is the best treatment in silage making using mixture of lelehanak-kume grass as it shows the highest OM content and had no significant difference with CN20 in CP content.